Recycling of typical supercapacitor materials. Issue 4 (April 2016) - Vermisoglou, Eleni C; Giannouri, Maria; Todorova, Nadia; Giannakopoulou, Tatiana; Lekakou, Constantina; Trapalis, Christos
A simple, facile and low-cost method for recycling of supercapacitor materials is proposed. This process aims to recover some fundamental components of a used supercapacitor, namely the electrolyte salt tetraethyl ammonium tetrafluoroborate (TEABF4 ) dissolved in an aprotic organic solvent such as acetonitrile (ACN), the carbonaceous material (activated charcoal, carbon nanotubes) purified, the current collector (aluminium foil) and the separator (paper) for further utilization. The method includes mechanical shredding of the supercapacitor in order to reduce its size, and separation of aluminium foil and paper from the carbonaceous resources containing TEABF4 by sieving. The extraction of TEABF4 from the carbonaceous material was based on its solubility in water and subsequent separation through filtering and distillation. A cyclic voltammetry curve of the recycled carbonaceous material revealed supercapacitor behaviour allowing a potential reutilization. Furthermore, as BF4 − stemming from TEABF4 can be slowly hydrolysed in an aqueous environment, thus releasing F − anions, which are hazardous, we went on to their gradual trapping with calcium acetate and conversion to non-hazardous CaF2 .